PENDEKATAN PSIKOLOGI DALAM STUDI ISLAM - Haris, Munawir (Palita: Journal of Social Religion Research, 2017)
The present religious presence is required to be active in solving the problems and challenges facing its adherents. The position and role of religion is not only a symbol of piety but can play a role in solving the existing problems. The psychological approach in Islamic studies has a significant role to explain the outward symptoms of religious people. Armed with psychological theories will be easy to know the level of religion that is understood, lived and practiced by someone. The cognitive theory of religion is able to provide answers related to the limitations beyond human capabilities. In addition, religious-based psychotherapy is one concept of psychotherapy in the perspective of Islam that can be used as a therapy to cure various diseases both physical and mental disorders.